Boisduval Scale, Diaspis boisduvalii Signoret (Insecta: Hemiptera: Diaspididae) - Adriana Espinosa; Heidi Bowman; Amanda Hodges; Greg Hodges (EDIS)
EENY467, a 6-page illustrated fact sheet by Adriana Espinosa, Heidi Bowman, Amanda Hodges, and Greg Hodges, is part of the Featured Creatures collection. It describes this economically important pest of orchids in Florida — distribution, description, life cycle, hosts, damage, and management. Includes references. Published by the UF Department of Entomology and Nematology, November 2009.